Femmes et religions, entre soumission et espace pour s’exprimer et agir, un regard d’historienne - Mathilde Dubesset (Nuevo mundo - Mundos Nuevos, 2008)
One cannot deny the role played by religious traditions in sex inequalities. The mark of apatriarchal culture is unmistakable in Judaism, Christianity and Islam, religions of the Book and theOnly God,  thought of as male. This mark can be detected in the interpretation of the main foundingtexts,  in the defiance towards women, in the masculine monopoly upon religious power and access to all that is Holy. Yet, some women have managed to gain opportunities for expression and action, within the framework of organised religion or by way of their religious culture. Musician nuns in the Middle Ages,  lady missionaries, God adventurers,  mother superiors –with true power – of 19th century catholic congregations, protestant women involved in women’s emancipation movements of the early 1900’s and, closer to us, feminist theologians revisiting the Bible : so many situations, over the centuries, that may lead to qualify one’s critical view of religions’ role in “the misfortune of women”, even though paradoxes are a-plenty (in the catholic world for instance). As for women who call themselves both feminists and Muslims, they challenge standard representations and illustrate the ever-surprising interrelation between women and religions.